حكاية القرآن للأقوال وموقفه منها - فرحات, كلثوم; جرادي, مريم (University of Eloued جامعة الوادي, 2020)
"الحمد لله رب العالمين والصلاة والسلام على إمام المرسلين وعلى آله وصحبه أجمعين، وبعد: هذا البحث مقدم لنيل شهادة الماستر بعنوان: حكاية القرآن للأقوال وموقفه منها، حاولنا من خلاله أن نبيّن ماهية الأقوال المحكية في القرآن وكيف كان موقفه منها، من خلال تتبع جميع الأقوال المحكية في القرآن على لسان المخلوقات ثم تصنيفها من خلال فصلين؛ الفصل الأول اعتمدنا فيه تصنيف الأقوال بحسب قائليها من بشر وملائكة وجن وحيوان وجماد، والفصل الثاني صنفنا فيه الأقوال المحكية بحسب موقف القرآن منها إقرارا أو إبطالا أو سكوتا عن المحكي مع مناقشة منهج القرآن في بيان موقفه، ومن أهم النتائج التي وقفنا عليها من خلال بحثنا هي أن الأقوال وردت بصيغ تليق بإعجاز القرآن وقد استغرقت الأقوال المحكية في القرآن جميع المخلوقات، وجلّ الأقوال المحكية ورد معها ردّ إما بالإقرار أو الإبطال وقلة من الأقوال سكت عنها القرآن. "Praise to Allah, Lord of the Worlds, and prayers and peace be upon the Imam of the Messengers and his family and companions, and after: This research is presented for obtaining a master’s testimony under the title: The Coran's Story of Sayings and its position Toward it. We tried to show throughout this study the definition of the told sayings in the Coran and how was its attitude towards them , by tracing all the told sayings in the Coran by humans. It was classified in two chapters. In the first chapter, we tend to classify sayings according to those who said them, including human beings, angels, jinns, animals and inanimate objects. The second chapter we classified the told sayings according to the Coran's position on them as approval, nullification, or silence about the tells, along with discussing the Coran's approach in explaining its position .One of the most important results that we came upon through our research is: The sayings came in a suitable way to the miracle of the Coran. The told sayings in the Coran included all creatures, and most of the told sayings came with a response, either by affirmation or nullification. Few of them about which the Coran remained silent.
مذكرة ماستر تخصص تفسير وعلوم قرآن
Keywords: "حكاية أقوال القرآن تصنيف موقف إقرار ردّ سكوت"; "tale Sayings The Quran rating Attitude Endorsement Reply Scott"